SISTEM INFORMASI AKUNTANSI KEUANGAN SEBAGAI ANALISIS PERENCANAAN LABA KOPERASI DENGAN MENGGUNAKAN METODE COST VOLUME PROFIT BERBASIS WEB. - Sri Wahyuning; Dewi Retno Putri (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
The research was conducted at KSPPS Mitra Amanah Sejahtera Abadi. Which is located at Ds. Sidorejo Rt. 02 / Rw. 05 Kec. Brangsong Kab. Kendal. Data recording and management previously applied to the MASA Cooperative is still manual. Transaction data such as daily dropping, dropping per AO, daily withdrawals and general ledgers and journals will be entered manually into the book.This study aims to facilitate the presentation of the profit planning analysis report which is applied to the cooperative each year. The use of bookkeeping that has been applied so far is felt to have several weaknesses which cause several problems. Therefore, cooperatives need to develop a new system, namely a computer-based financial accounting information system.The Cost Volume Profit method is expected to be able to carry out good profit planning and more valid financial records so that it can reduce the risk of errors and the process is much faster.